Effects of Awake Prone Positioning on the Clinical Evolution of Adults Admitted for COVID-19 at the Highest Complexity Hospital in Araucanía region, Chile (Revista de Medicina Clinica, 2024)
Introduction: TTo analyze the effects of awake prone positioning on the clinical evolution of adults hospitalized for COVID-19. Patients and methods: Prospective cohort in Hernán Henríquez Hospital, Temuco-Chile. All subjects admitted between March and September 2020 with a diagnosis of COVID-19 were included. Main variables of interest: The exposure factor was awake prone positioning and the result was the requirement for invasive mechanical ventilation (IMV) and mortality. Results: The cohort was composed of 346 subjects, with an average age of 57 years; 52% were men, and 37% had two or more comorbidities. Of the cohort studied, 20% required prone awake therapy, and among them, the average number of days in prone awake positioning was three days, 28% required IMV support with an average use of 14 days. Baseline clinical characteristics did not show significant differences between subjects who were positioned prone and those who did not undergo this treatment. Logistic regression models adjusted for age, sex, comorbidities and use of high-flow nasal cannula (HFNC) showed a decreased risk of requiring IMV in subjects positioned awake prone [Odds Ratio (OR) = 0.362, Confidence Interval (CI)= 0.16-0.77, p=0.009]. There are clinically relevant differences in the survival curve between those with awake prone positioning. However, the adjusted Cox regression model did not show significant differences [Hazard Ratio (HR)= 0.63 (CI)= 0.18-2.17, p=0.46. Conclusion: Prone awake positioning is associated with lower IMV requirements.
Keywords: COVID-19; Awake Prone; Mortality; Invasive Mechanical Ventilation